Raman scattering studies of (GaP)(n)/(InP)(n) (n=1, 1.7, 2) short-period superiattice structures - Rho, H.; Lim, J-R.; Song, J. D.; Choi, W. J.; Lee, Y. T. (WILEY, 2009)
We report Raman scattering from (GaP)(n)(InP)(n) (n = 1, 1.7, 2) short-period superlattice (SPS) structures to study the effect of lateral composition modulation (LCM) on the behavior of optical phonons. Cross-sectional transmission electron microscope images revealed that LCM was formed with complex pattern in the n = 1.7 and n = 2 samples grown at 490 degrees C. Interestingly, both the InP- and the GaP-like longitudinal optical (LO) phonon energies increased systematically as the number of monolayers was increased from n = 1 to n = 2. A significant broadening of the phonon line shapes was also observed for the n = 1.7 and n = 2 samples. In contrast, for samples grown at 425 degrees C, both the increase of the LO phonon energies and the broadening of the phonon line shapes were observed only when n = 1.7. Our results demonstrate that the optical phonons in the (GaP)(n)/(InP)(n) SPS structures are significantly affected in the occurrence of LCM related to the growth temperature and the number of monolayers. Copyright (C) 2009 John Wiley & Sons, Ltd.
Keywords: LATERAL COMPOSITION MODULATION; PHASE-SEPARATION; SUPERLATTICES; INITIATION; EVOLUTION